2010
DOI: 10.1088/0004-637x/710/1/836
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Dependence of the Centroid Frequency and Phase Lag of the Quasi-Periodic Oscillations in GRS 1915+105

Abstract: We present a study of the centroid frequencies and phase lags of the quasiperiodic oscillations (QPOs) as functions of photon energy for GRS 1915+105.It is found that the centroid frequencies of the 0.5-10 Hz QPOs and their phase lags are both energy dependent, and there exists an anti-correlation between the QPO frequency and phase lag. These new results challenge the popular QPO models, because none of them can fully explain the observed properties. We suggest that the observed QPO phase lags are partially d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
80
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 38 publications
(57 reference statements)
17
80
0
Order By: Relevance
“…GRS 1915+105 has QPO lags that evolve from hard to soft (Reig et al 2000;Qu et al 2010); GX 339-4 has hard QPO lags for the full range of observed QPO frequencies, while the time lags of all ULX QPOs appear to be soft. The difference in time lag between the two kinds of QPOs (type-C QPO in BHXRBs and ULX QPOs) suggests a different physical process.…”
Section: Type Of Qpomentioning
confidence: 99%
See 3 more Smart Citations
“…GRS 1915+105 has QPO lags that evolve from hard to soft (Reig et al 2000;Qu et al 2010); GX 339-4 has hard QPO lags for the full range of observed QPO frequencies, while the time lags of all ULX QPOs appear to be soft. The difference in time lag between the two kinds of QPOs (type-C QPO in BHXRBs and ULX QPOs) suggests a different physical process.…”
Section: Type Of Qpomentioning
confidence: 99%
“…Much research has been based on time lag calculations in StBHs, NSs, and AGNs. BHB Cyg X-1 shows a hard time lag in a broad frequency range (Van der Klis et al 1987;Cui et al 1997;Nowak et al 1999aNowak et al , 1999b), while GRS 1915+105 shows an evolution from hard to soft lag of the Type-C QPO (Reig et al 2000;Qu et al 2010). Barret (2013) investigated the soft lag in the NS 4U 1608-522 kHz QPO and suggests that this may involve reverberation.…”
Section: -10mentioning
confidence: 99%
See 2 more Smart Citations
“…The LFQPO amplitude increases with photon energy and it turns over in high energy bands in some cases (e.g., Tomsick & Kaaret 2001;Rodriguez et al 2002bRodriguez et al , 2004Zdziarski et al 2005). As the centroid frequency of LFQPO increases, the corralation between LFQPO frequency and photon energy evolves from negative to positive (Qu et al 2010). In addition, three more combined patterns of negative to positive correlation were discovered (Yan et al 2012).…”
Section: Introductionmentioning
confidence: 99%